Brain Spontaneous Intracranial Hypotension Score for Treatment Monitoring After Surgical Closure of the Underlying Spinal Dural Leak - Dobrocky, Tomas; Häni, Levin; Rohner, Roman; Branca, Mattia; Mordasini, Pasquale; Pilgram-Pastor, Sara; Kaesmacher, Johannes; Cianfoni, Alessandro; Schär, Ralph T.; Gralla, Jan; Raabe, Andreas; Ulrich, Christian; et al. (Clinical neuroradiology (Munich), 2022)
Background Spontaneous intracranial hypotension (SIH) is a debilitating condition requiring effective treatment; however, objective data on treatment response are scarce. Purpose To assess the suitability of the brain MRI-based SIH score (bSIH) for monitoring treatment success in SIH patients with a proven spinal cerebrospinal fluid (CSF) leak after microsurgical closure of the underlying dural breach. Methods This retrospective cohort study included consecutive SIH patients with a proven spinal CSF leak, investigated at dedicated referral centre January 2012 to March 2020. The bSIH score integrates 6 imaging findings; 3 major (2 points) and 3 minor (1 point), and ranges from 0 to 9, with 0 indicating low and 9 high probability of spinal CSF loss. The score was calculated using brain magnetic resonance imaging (MRI) before and after surgical treatment of the underlying CSF leak. Headache intensity was registered on a numeric rating scale (NRS) (range 0–10). Results In this study 52 SIH patients, 35 (67%) female, mean age 45.3 years, with a proven spinal CSF leak were included. The mean bSIH score decreased significantly from baseline to after surgical closure of the underlying dural breach (6.9 vs. 1.3, P < 0.001). A decrease in the NRS score was reported (8.6 vs. 1.2, P < 0.001). Conclusion The bSIH score is a simple tool which may serve to monitor treatment success in SIH patients after surgical closure of the underlying spinal dural leak. Its decrease after surgical closure of the underlying spinal dural breach indicates restoration of an equilibrium within the CSF compartment.